United States : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2003)
This Selected Issues paper analyzes the United State's (U.S.) household savings role in supporting the U.S. recovery; and focuses on the market for single-family housing, and the importance for household balance sheets. It discusses the underfunding of corporate pension plans, macroeconomic, and policy implications; the U.S. fiscal position, and reviews the causes of the fiscal crisis. It examines the impact of energy shocks, energy policy, and the taxation role. It analyzes the growth in linkages between the United States and other G-7 countries, and the regional and bilateral trade links issues.